Teachers' and Students' Experiences in Implementing Direct Instruction in Islamic Religious Education Learning: A Hermeneutic Phenomenological Perspective - Abu Warasy Batula; Nurlaila Turohmah; Robiatul Adawiyah Ramadhani; Pitra Gosha Patriasya (Cultura Islamica: Journal of Islamic Studies, Management, and Culture, 2026)
This phenomenological hermeneutic study explores the lived experiences of teachers and students in implementing the Direct Instruction (DI) model in Islamic Religious Education (PAI) at the senior high school level. Using Max van Manen's hermeneutic phenomenology approach, this research investigates the pedagogical and spiritual meanings embedded in structured instructional practices. Data were collected through in-depth interviews with PAI teachers and students at SMA Negeri 2 Bandung, complemented by participatory observation and documentation. The findings reveal that Direct Instruction in PAI transcends its technical-procedural nature, functioning as a medium for spiritual internalization of Islamic values such as discipline, responsibility, and sincerity. Teachers experience tension between procedural demands and the search for spiritual meaning in teaching, while students perceive a shift from merely receiving instructions to discovering religious meaning through structure and clarity. This study introduces the concept of "Spiritualized Direct Instruction," integrating the effectiveness of DI with Islamic spiritual values and educational ethics. The research contributes to the development of PAI learning theory that harmonizes modern pedagogical models with Islamic spirituality, offering practical implications for curriculum developers and educators in creating meaningful religious education experiences.